THE EFFECT OF CAPITAL ADEQUACY, LIQUIDITY AND FIRM SIZE ON EARNINGS MANAGEMENT WITH CORPORATE GOVERNANCE AS MODERATING VARIABLES IN CONVENTIONAL BANKING LISTED ON IDX 2015 – 2019 - Citra, Kharisma; Faisal, Yusuf; Wibisono, Chablullah; Gumala Sari, Egi (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2021)
With corporate governance as a moderating variable, this study intends to examine the impact of capital adequacy, liquidity, and firm size on earnings management. This study's population consists of 45 conventional banks that were listed on the Indonesia Stock Exchange between 2015 - 2019. Purposive sampling was used to choose the sample, which resulted in a total sample of 33 firms. Multiple regression analysis using Eviews 9 software is the analytical technique used to test the hypothesis. The results of this study indicate that the capital adequacy variable has a significant effect and liquidity has an insignificant effect, both of which have a negative coefficient value, while firm size has a significant effect on earnings management with a significant coefficient value. positive. Meanwhile, corporate governance is able to moderate the effect of capital adequacy on earnings management and is unable to moderate the effect of liquidity on earnings management with a decreasing t-statistic value, while corporate governance is able to moderate the effect of t-statistics value. Simultaneously, capital adequacy, liquidity, firm size and being moderated by corporate governance have a significant effect on earnings management